Spatial Orientation In Sportsmen - Stoyanova, Stanislava; Ivantchev, Nikolay; Petrova, Kremka (European Scientific Journal, ESJ, 2016)
Cognitive processes are important for successful practicing of sport. 69 national and regional competitors in different kinds of sports were studied by means of 2D Visualisation, the subtest â€œComparing surfacesâ€ of AHA and GESTA - computerized test methods from Vienna Test System measuring spatial orientation, precision of estimation of the size of the surfaces, and perception of more or few details in visual environment respectively. There were not any significant gender differences in athletesâ€™ spatial orientation. Longer period of sports training was related to better spatial orientation.